Pengaruh Fasilitas Terhadap Physical Motivation Pengunjung Di Daya Tarik Taman Wisata Alam Rimbo Panti Kabupaten Pasaman - Ressy Astri Ramadhani; Dwi Pratiwi Wulandari (Universitas Katolik Widya Karya Malang, 2023)
This research was motivated by an error related to physical motivation at the Rimbo Panti Nature Park (TWA) which was allegedly caused by the facilities at the Rimbo Panti TWA. This study aims to analyze the effect of facilities on the physical motivation of visitors at the Rimbo Panti TWA attraction. This type of research is quantitative with a causal associative approach. This research was conducted at the attraction of TWA Rimbo Panti, Panti District, Pasaman Regency. The population of this study were visitors who had come to the TWA Rimbo Panti charm, totaling 7,319 people. Selection of research samples using incidental sampling with a total sample of 99 people. Data collection uses a Likert scale model questionnaire that has been tested for validity and reliability, then the research data uses simple linear regression. The results of this study show that 59.6% of respondents stated that the TWA Rimbo Panti facilities were not in good condition, then on the physical motivation variable 79.8% of respondents assessed that they did not feel physical motivation. Then the two variables were analyzed and the result was that there was an influence of facilities on physical motivation of 77.5%.